THEORETICAL AND PRACTICAL ISSUES OF EXEMPTION FROM CRIMINAL LIABILITY UPON COMPENSATION FOR DAMAGE CAUSED - Urazaliev Murod Koraevich (PT. Antis International Publisher, 2026)
The humanization of criminal law and the reduction of the repressive nature of punishment constitute key priorities of state policy in the Republic of Uzbekistan, aimed at ensuring justice, legality, and effective protection of individual rights. Within this framework, exemption from criminal liability and punishment upon compensation for damage caused occupies an important place, as damage resulting from socially dangerous acts may be material, physical, or moral, and its nature and extent directly influence crime qualification and legal consequences. Despite extensive legislative regulation and foreign experience, compensation for damage is not systematized in Uzbek criminal law as an independent legal institution, but is mainly applied as an auxiliary element within reconciliation or genuine repentance, leading to legal ambiguities and inconsistent law enforcement practice. The study aims to analyze the theoretical and practical foundations of exemption from criminal liability and punishment upon compensation for damage, identify existing legal conflicts, and substantiate proposals for improving criminal legislation. The analysis demonstrates that full, voluntary, active, and lawful compensation for damage serves as a reliable indicator of reduced social danger and genuine remorse, while comparative analysis shows that many foreign legal systems recognize compensation as an independent ground for exemption or mitigation of punishment. The study offers a comprehensive doctrinal justification for distinguishing exemption from liability upon compensation for damage as a separate criminal-law institution, based on national legislation and comparative legal analysis. The findings support the introduction of an independent institution of exemption from criminal liability and punishment upon compensation for damage in the Criminal Code of Uzbekistan, which would enhance legal certainty, strengthen victim rights protection, promote timely restoration of harm, and further advance the principles of justice and proportionality in criminal justice policy.